Effect of Grinding and Pelleting Sorghum Grain Varieties with a Hammermill on Subsequent Particle Size, Flowability, and Pelleting Durability Index - Walter G. Friesen; Haley K. Ottot; Charles R. Stark; Chad B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2024)
Two experiments were conducted to determine the processing characteristics of yellow corn and three varieties of sorghum grain: red non-waxy, red waxy, and white waxy. Experiment 1 was conducted with consistent hammermill parameters to determine the impact of each respective grain source on subsequent particle size (dgw), standard deviation (Sgw), and angle of repose (AoR). The four grain sources ground within the first experiment were then formulated into diets to be manufactured into pelleted feed. All pelleting parameters were held consistent throughout the duration of the experiment to determine the effects of different grain sources on the pelleting process and subsequent pellet durability index (PDI). Results within exp. 1 determined the four grain sources to have different dgw values. To account for the confounding factor of particle size, exp. 2 was conducted with the same experimental design, however, aimed to achieve a consistent target dgw within each of the four grain types. Data were analyzed as a randomized block design using the GLIMMIX procedure in SAS v9.4. When grinding with consistent hammermill parameters, dgw was greater (P = 0.001) in both waxy varieties of sorghum when compared to red non-waxy sorghum and yellow corn. Yellow corn had a greater (P < 0.001) Sgw when compared to that of the sorghum grain varieties. Waxy sorghum grain had improved (P < 0.001) AoR in comparison to the other grain sources. When grinding to a consistent particle size, the sorghum varieties had improved AoR values (P < 0.001) when compared to yellow corn. Finally, both red and white waxy sorghum-based diets had improved PDI (P < 0.05) within both experiment 1 and 2 when compared to red non-waxy and yellow corn-based diets. In conclusion, waxy sorghum grain had significant impacts in feed processing characteristics such as a greater dgw and an improved PDI when compared to yellow corn, thus representing possible improvements for feed processing quality when using these respective varieties of sorghum grain.
Keywords: particle size; pellet quality; sorghum grain processing; sorghum grain variety